Relationship between serum uric acid levels and uric acid lowering therapy with the prognosis of patients with heart failure with preserved ejection fraction: a meta-analysis - Li, Linzhi; Chang, Ying; Li, Fei; Yin, Yuehui (Frontiers in Cardiovascular Medicine, 2024)
Aims: This meta-analysis aimed to explore the association between serum uric acid levels and the efficacy of uric acid-lowering therapies on clinical outcomes among patients with heart failure with preserved ejection fraction (HFpEF).: A comprehensive literature search was conducted through October 21, 2023, across PubMed, Embase, Cochrane Library, and Web of Science databases. The pooled effect sizes were estimated and presented with their respective 95% confidence intervals (CI). Subgroup analyses were conducted based on various factors, including sample size (< 1000 versus ≥ 1000), follow-up duration (< 2 years versus ≥ 2 years), study quality (assessed by a score of < 7 versus ≥ 7), ethnicity (Non-Asian versus Asian), study design (prospective versus retrospective), type of heart failure (HF) (acute versus chronic), presence of hyperuricemia (yes or no), left ventricular ejection fraction (LVEF) thresholds (≥ 45% versus ≥ 50%), and the type of uric acid-lowering therapy (traditional versus novel).The analysis included a total of 12 studies. Elevated serum uric acid levels were significantly linked to an increased risk of all-cause mortality [relative risk (RR):1.21, 95% CI: 1.06 to 1.37, P =0.004] and cardiovascular (CV) mortality (RR: 1.71, 95% CI: 1.42 to 2.04, P <0.001) in HFpEF patients. Subgroup analyses confirmed this association, particularly in non-Asian populations, those with chronic HFpEF, and studies with a follow-up duration of two years or more. Additionally, higher uric acid levels were associated with an increased risk of HF-related hospitalization [hazard ratio (HR): 1.61, 95% CI: 1.12 to 2.34, P =0.011]. Regarding treatment, uric acid-lowering Uric acid levels and uric acid-lowering therapy on HFpEF 3 therapy did not show a significant effect on reducing mortality in HFpEF patients.However, it was associated with a decreased risk of hospitalization due to HF (RR: 0.85, 95% CI: 0.79 to 0.91, P <0.001).The findings of this study highlight the prognostic significance of serum uric acid levels in HFpEF and suggest that uric acid-lowering therapy may be beneficial in reducing the incidence of HF hospitalizations. Further research is warranted to elucidate the mechanisms by which uric acid-lowering therapy confers its potential benefits.Uric acid levels and uric acid-lowering therapy on HFpEF